En lampa av naturen : Smarta materialkombinationer för att minska miljöpåverkan av en produkt - Olofsson, Lukas (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2021)
The report contains an account of a development project done during 10 weeks of the spring semester at Luleå University of Technology 2021. The project is done as a final thesis for the program Bachelor of Science with a focus in industrial design. The development project resulted in a prototype lamp. The functioning prototype is an embodied union of the perspectives environment and living environment. Through smart lighting of the home, the living environment, a room can become more flexible and adaptable. It is easier to install new lighting than it is to move a wall. The lamp is created to improve lighting and spaciousness. A light source's use of contrasts and illumination in all directions can make a room feel more comfortable to be in and larger than it is. The environmental perspective is based on materials science. When designing new products, a factor that controls the product's climate footprint and environmental impact is the choice of material. Greater and greater value is placed in the environmental impact of products and consumers have actively begun to influence their buying behaviors based on striving for a better relationship with the environment, this work has taken advantage of. A biocomposite has therefore been created consisting of a matrix material of potato plastic combined with fiber reinforcement made from dried fruit residues from juice production. Especially potatoes and carrots. This gives a result of a 100% bio-based material. The work has followed an iterative process and used creative methods to stimulate innovation and solutions. A great focus has been placed on the prototype's material and the production of samples of biocomposites. Which has given rise to a lamp whose aesthetics are governed by the material. The lamp has a function of giving off two completely different looks when it is on and off. In an off position, the hardness of the material is emphasized, and when it is lit, it comes to life. Like a sun hanging from the ceiling, the lamp extends the days into the night. ...